2020
DOI: 10.1051/bioconf/20202004005
|View full text |Cite
|
Sign up to set email alerts
|

Blood glucose level of white rats (Rattus norvegicus) after giving catfish biscuit (Pangasius hypothalmus)

Abstract: Glucose is an important carbohydrate which is more absorbed into the bloodstream as glucose and other sugar is changed into glucose in the liver. Blood glucose level is closely related to diabetes mellitus. Diabetes mellitus is a disease that arises in a person which is indicated by the presence of blood glucose levels exceeding normal (hyperglycemia) due to the deficiency of the insulin hormone in the body. The design of this research was using RAL with 24 male rats that divided into 6 treatments which were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…The hyperinsulinemic and hyperglycemic parameters showed the insulin resistance condition of the animal. In normal condition, rat fasting serum insulin level is <25 mIU/L and for blood glucose normal level is 50 -135 mg/dL (Hidayaturrahmah et al, 2020). Figures 2 showed increased the level of insulin and blood glucose level after administration of hyperchaloric diet for 16 weeks.…”
Section: Resultsmentioning
confidence: 94%
“…The hyperinsulinemic and hyperglycemic parameters showed the insulin resistance condition of the animal. In normal condition, rat fasting serum insulin level is <25 mIU/L and for blood glucose normal level is 50 -135 mg/dL (Hidayaturrahmah et al, 2020). Figures 2 showed increased the level of insulin and blood glucose level after administration of hyperchaloric diet for 16 weeks.…”
Section: Resultsmentioning
confidence: 94%
“…The measurement of malondialdehyde is not only through plasma and serum, but also from various tissues in kidney tissues in patients with diabetes. 9 According to Hidayaturrahmah et al (2020) 43 blood glucose levels in normal rats ranged from 50-135 mg/dl. 43 In Table 1, it can be seen that the average levels of blood glucose on the day 0 for all treatments were in normal rates, 66.29-68.40 mg/dl.…”
Section: Resultsmentioning
confidence: 99%
“…9 According to Hidayaturrahmah et al (2020) 43 blood glucose levels in normal rats ranged from 50-135 mg/dl. 43 In Table 1, it can be seen that the average levels of blood glucose on the day 0 for all treatments were in normal rates, 66.29-68.40 mg/dl. Similarly, in the same table, it was also shown that blood glucose levels in the experimental rats in the normal control on the measurement day 0, 3, and 18 were in normal rates; these groups shown to imply that all animal models were not diabetic without STZ-NA induction.…”
Section: Resultsmentioning
confidence: 99%
“…The normal blood glucose level in rats is 50-135mg/dL [41]. The results of the effect of sardine sh oil and njansan oil on the serum blood glucose level of obese Wistar rats are shown in Fig.…”
Section: Effect Of Sardine Sh Oil and Njansan Oil On Serum Blood Gluc...mentioning
confidence: 94%